2021
DOI: 10.1017/s0022215121004205
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes of nasal mucosa after nasal packing with Merocel

Abstract: Objective To determine histopathological changes in nasal mucosa associated with duration of nasal packing with Merocel tampons. Methods This study included 24 healthy rabbits, 6 rabbits per group. In group A, no tampon was applied. In group B, Merocel nasal tampons were applied and removed after 24 hours. In group C, the tampons were removed after 48 hours. In group D, the tampons were removed after 5 days. Specimens were obtained from the septum of each rabbit, including cartilage. His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Merocel tampons induce histopathological changes in the nasal mucosa characterized by degeneration and dysplastic changes in epithelial cells in addition to inflammation and mucosal edema in the subepithelium within 24 hours of insertion. 12 Moreover, inflammation is a well-known etiology of CDI as Hayashi et al found in their study on six patients with Rathke cleft cyst. The authors discussed that the mechanism behind delayed DI occurrence can be attributed to the spreading of inflammatory chemicals from the cyst content into the area of the pituitary gland.…”
Section: Discussionmentioning
confidence: 95%
“…Merocel tampons induce histopathological changes in the nasal mucosa characterized by degeneration and dysplastic changes in epithelial cells in addition to inflammation and mucosal edema in the subepithelium within 24 hours of insertion. 12 Moreover, inflammation is a well-known etiology of CDI as Hayashi et al found in their study on six patients with Rathke cleft cyst. The authors discussed that the mechanism behind delayed DI occurrence can be attributed to the spreading of inflammatory chemicals from the cyst content into the area of the pituitary gland.…”
Section: Discussionmentioning
confidence: 95%